Translational Justice in a Multilingual World: An Overview of Translational Regimes - Meylaerts, Reine (Meta, 2011)
Since democratic societies are based on the ideal of participatory citizenship and since participatory citizenship presupposes, among other things, the citizens’ right to communicate with the authorities, one of the biggest challenges for contemporary multilingual societies is the elaboration of a fair translation policy: there is no language policy without a translation policy. However, among the numerous studies on language rights, on language policies or on immigrant incorporation, the key role of translation is usually not taken into consideration. Which linguistic and translational territoriality regimes are used by authorities to communicate with their multilingual populations? How do these different regimes relate to their linguistic and translational rights and their chances for participatory citizenship and integration? This essay discusses four prototypical regimes which may be used by authorities to communicate with their citizens. It will also try to hint at their possible impact on minorities’ linguistic and translational rights and integration.